UTAUT-Based Analysis of Factors Associated with Microsoft Teams Use in Digital Learning among Undergraduate Students - Cintya Syarah Azzahra; Jap Tji Beng; Sri Tiatri; Fouad Nagm; Rahmiyana Nurkholiza; Vienchenzia Oeyta Dwitama Dinatha (Journal of Information System and Informatics, 2026)
This study examined factors influencing Microsoft Teams adoption in digital learning using the Unified Theory of Acceptance and Use of Technology (UTAUT). A quantitative cross-sectional survey was conducted with 268 undergraduate students, and data were analyzed using reliability testing, Confirmatory Factor Analysis (CFA), classical assumption testing, and multiple linear regression. The results showed that Performance Expectancy, Effort Expectancy, and Social Influence significantly influenced Behavioral Intention, while Facilitating Conditions and Behavioral Intention significantly influenced Use Behavior. The model explained 60.2% of the variance in Behavioral Intention and 46.4% of the variance in Use Behavior. CFA demonstrated acceptable fit for most indices, although RMSEA indicated marginal fit. Performance Expectancy was the strongest predictor of Behavioral Intention, whereas Behavioral Intention was the strongest predictor of Use Behavior. Unlike previous studies focusing primarily on Behavioral Intention, this study also examined its relationship with self-reported Use Behavior among Indonesian undergraduates. The findings highlight the importance of usefulness, ease of use, social support, and facilitating conditions in promoting Microsoft Teams adoption for digital learning.